PHARMACODYNAMICS STUDY OF ETHANOL EXTRACT OF CYCLEA BARBATA (MIERS.) LEAVES ON SRF AND COX-2 GASTRIC MICE WITH NSAID GASTROPATHY - Florence Pribadi; Suhartati Suhartati; Achmad Basori (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2017)
Epidemiology of NSAIDs gastropathy is increasing as increase number of usage. From arthritis to cardiovascular events and cancer prevention, the versatility of NSAIDs is not questioned. However, no dose of NSAIDs is safe. No matter low dose, or single use, NSAIDs will cause gastric damage upto 3-7 days after use. In inflammation and healing process of gastropathy there are various proteins involved, but treatment with COX-2 and SRF are associated with an immediate healing and better quality of gastric mucosa. Cyclea barbata (miers.) has been declared as functional food for preventing and treatment gastropathy yet, its mechanism of actions have not yet clearly discovered. Hence the aim of this study is to analyze the effects of Cyclea barbata (miers.) ethanol extract to COX-2 and SRF in gastric tissue, in time series basis. Laboratory mice was induced with aspirin to produce gastropathy and then treated with Cyclea barbata (miers.) extract for 1, 3, 7, 10 or 14 days. Gastric tissue then harvested and analysed with elisa procedure to determine tissue SRF and COX-2 level. Treatment was proven to increase COX-2 and SRF higher than control group. This concludes one of Cyclea barbata (miers.) mechanism for NSAIDs gastropathy is by increasing tissue COX-2 and SRF.